Strengthening Indigenous Village Government Institutions through Governance Innovation and Community Empowerment - Susilawaty, Susilawaty; Tambawang, Laela (Musamus Journal of Public Administration, 2024)
The indigenous village government institutions play a crucial role in preserving local wisdom and supporting sustainable development in indigenous areas. However, challenges in governance and the lack of community empowerment often hinder their effectiveness. This study aims to identify effective governance innovations and empowerment programs that can strengthen these institutions. Using a qualitative method through case studies in several indigenous villages in Indonesia, data were collected through in-depth interviews, participatory observation, and document analysis. The results show that innovations in governance, such as digitalization and increased transparency, along with community empowerment programs through skill training, significantly improve the performance of indigenous village government institutions. Additionally, community participation in the planning and implementation of village development programs has increased, fostering local economic self-reliance. These innovations also help reduce dependency on the central government and enhance the overall quality of life in the villages. In conclusion, strengthening indigenous village government institutions through governance innovation and community empowerment positively contributes to more effective local resource management and active participation in village development.